2002
DOI: 10.1080/13550280290100914
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids and Central Nervous System Inflammation

Abstract: Glucocorticoids (GCs) are well known for their anti-inflammatory and immunosuppressive properties in the periphery and are therefore widely and successfully used in the treatment of autoimmune diseases, chronic inflammation, or transplant rejection. This led to the assumption that GCs are uniformly anti-inflammatory in the periphery and the central nervous system (CNS). As a consequence, GCs are also used in the treatment of CNS inflammation. There is abundant evidence that an inflammatory reaction is mounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 213 publications
2
21
0
Order By: Relevance
“…Glucocorticoids have well-known immunosuppressive properties in the peripheral immune system which make them clinically useful for the treatment of autoimmune diseases, chronic inflammation, or to avoid transplant rejection (Dinkel et al, 2002). The rapid increase of glucocorticoid circulating levels after systemic inflammatory challenge has been interpreted as a protective, antiinflammatory response (Nadeau and Rivest, 2003;Nakano et al, 1987); in agreement, adrenalectomy results in a 40-fold increase in the lethal effects of LPS (Koniaris et al, 2001).…”
Section: Glucocorticoid Receptors In Microgliasupporting
confidence: 54%
“…Glucocorticoids have well-known immunosuppressive properties in the peripheral immune system which make them clinically useful for the treatment of autoimmune diseases, chronic inflammation, or to avoid transplant rejection (Dinkel et al, 2002). The rapid increase of glucocorticoid circulating levels after systemic inflammatory challenge has been interpreted as a protective, antiinflammatory response (Nadeau and Rivest, 2003;Nakano et al, 1987); in agreement, adrenalectomy results in a 40-fold increase in the lethal effects of LPS (Koniaris et al, 2001).…”
Section: Glucocorticoid Receptors In Microgliasupporting
confidence: 54%
“…In a previous study, we found that tropical House Sparrows invest more in immune defense (Martin et al, in revision a) and rely on diVerent immune cell populations (lymphocytes) than their temperate counterparts when mounting PHA responses (Martin et al, in revision b). Thus, the immunological insensitivity to CORT we found in this experiment could be a consequence of the same challenge inducing diVerent types of immune activity in each population and only one of these types of defense being sensitive to CORT (Dinkel et al, 2002;Sapolsky et al, 2000). Indeed, had we measured a diVerent aspect of immune defense, we might have obtained a diVerent result altogether (Schmid-Hempel and Ebert, 2003).…”
Section: How Could Latitudinal Diverences In Cort and Its Evects On Imentioning
confidence: 71%
“…Indeed, had we measured a diVerent aspect of immune defense, we might have obtained a diVerent result altogether (Schmid-Hempel and Ebert, 2003). Other immune defenses, like antibody production and acute phase (fever) responses, may not be aVected by CORT in the same way as cutaneous immune function induced by PHA (Dinkel et al, 2002;Sapolsky et al, 2000).…”
Section: How Could Latitudinal Diverences In Cort and Its Evects On Imentioning
confidence: 99%
See 1 more Smart Citation
“…Since protein malnutrition can increase lipopolysaccharide-induced NFκB activation and proinflammatory cytokines in liver [32], we investigated whether PEM increases hippocampal NFκB activation in response to global ischemia. A second objective of the study was to address the possibility that PEM alters serum glucose or glucocorticoid levels since these physiological variables modify ischemic brain injury [33,34].…”
Section: Introductionmentioning
confidence: 99%